Analytical and experimental discussion of a circuit-based model for compact fluorescent lamps in a 60Hz power grid (2015)
This article presents an analysis and discussion on the performance of a circuit-based model for Compact Fluorescent Lamps (CFL) in a 120V 60Hz power grid. This model is proposed and validated in previous scientific literature for CFLs in 230V 50Hz systems. Nevertheless, the derivation of this model is not straightforward to follow and its performance in 120V 60Hz systems is a matter of research work. In this paper, the analytical derivation of this CFL model is presented in detail and its performance is discussed when predicting the current of a CFL designed to operate in a 120V 60Hz electrical system. The derived model is separately implemented in both MATLAB® and ATP-EMTP® software using two different sets of parameters previously proposed for 230V 50Hz CFLs. These simulation results are compared against laboratory measurements using a programmable AC voltage source. The measurements and simulations considered seven CFLs 110/127V 60Hz with different power ratings supplied by a sinusoidal (not distorted) voltage source. The simulations under these conditions do not properly predict the current measurements and therefore the set of parameters and/or the model itself need to be adjusted for 120V 60Hz power grids.